Chemical engineering design - Sinnott, R. K.; Towler, Gavin P. (Coulson & Richardson's chemical engineering series., 2020)
Chemical Engineering Design: SI Edition is one of the best-known and most widely used textbooks available for students of chemical engineering. The enduring hallmarks of this classic book are its scope and practical emphasis which make it particularly popular with instructors and students who appreciate its relevance and clarity. This new edition provides coverage of the latest aspects of process design, operations, safety, loss prevention, equipment selection, and much more, including updates on plant and equipment costs, regulations and technical standards.